Efektivitas Pembelajaran Berbasis STEAM dalam Meningkatkan Keterampilan Berpikir Kreatif di SDIT I'aanatuth Thalibiin Kec. Tualang - Afni, Meli; Delimunthe , Hasnah; Nikmah , Sukrun (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to analyze the effectiveness of Science, Technology, Engineering, Arts, and Mathematics (STEAM)-based learning in enhancing students' creative thinking skills at SDIT I'aanatuth Thalibiin, Tualang District. The research employs Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection in two cycles. The subjects are fifth-grade students who exhibit low creative thinking skills. Data were collected through observations, interviews, creative thinking skill tests, and documentation. The findings indicate that the implementation of STEAM-based learning significantly improves students' creative thinking skills. In the first cycle, creative thinking skills increased by 20%, and in the second cycle, they improved by 40%. The STEAM approach enables students to integrate various disciplines in problem-solving, thereby enhancing creativity and innovation. This study concludes that STEAM-based learning is effective in developing elementary school students' creative thinking skills.